Porous Organic Cages for Sulfur Hexafluoride Separation - Hasell, Tom; Miklitz, Marcin; Stephenson, Andrew; Little, Marc A; Chong, Samantha Y; Clowes, Rob; Chen, Linjiang; Holden, Daniel; Tribello, Gareth A; Jelfs, Kim E; Cooper, Andrew I (Journal of the American Chemical Society, 2016)
A series of porous organic cages is examined for the selective adsorption of sulfur hexafluoride (SF6) over nitrogen. Despite lacking any metal sites, a porous cage, CC3, shows the highest SF6/N2 selectivity reported for any material at ambient temperature and pressure, which translates to real separations in a gas breakthrough column. The SF6 uptake of these materials is considerably higher than would be expected from the static pore structures. The location of SF6 within these materials is elucidated by X-ray crystallography, and it is shown that cooperative diffusion and structural rearrangements in these molecular crystals can rationalize their superior SF6/N2 selectivity.